2017
DOI: 10.21660/2017.32.63655
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Microzonation Studies Considering Local Site Effects for Yogyakarta City, Indonesia

Abstract: An Mw 6.3 earthquake hit Yogyakarta, Indonesia in 2006, causing massive damage in this densely populated area. As a consequence, risk reduction efforts in terms of local seismic response and peak ground acceleration (PGA) mapping is needed to improve the spatial planning and early assessment before another disastrous earthquake. The determination of PGA for microzonation study was conducted by referring to the Indonesian seismic code and empirical prediction by examining attenuation relationships considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The model applied earthquake ground motions at the base of the soil column to analyze seismic wave propagation [12,13,14]. In this investigation, three seismic acceleration records from PEER NGA database were used.…”
Section: Seismic Motionmentioning
confidence: 99%
“…The model applied earthquake ground motions at the base of the soil column to analyze seismic wave propagation [12,13,14]. In this investigation, three seismic acceleration records from PEER NGA database were used.…”
Section: Seismic Motionmentioning
confidence: 99%
“…Non-linear earthquake site response analyses (NERA) is an excel-based software developed by Bardet and Tobita (2001) to calculate one-dimensional site response in layered soil, considering shear wave velocity at each layer and acceleration response spectrum (including PGA) as output [19]. Fathani and Wilopo (2017) have used the use of NERA in determining the PGA value for Yogyakarta City, and the result PGA value from NERA is higher than other methods (Attenuation function and microtremor) [20]. The output of NERA is dependent on ground motion input selection.…”
Section: Non-linear Earthquake Site-response Analysismentioning
confidence: 99%
“…However, there is a lack of comprehensive research regarding the determination of Peak Ground Acceleration at this specific location. Comparative research on PGA and PGA microzonation in Indonesia has only been conducted in Yogyakarta [2]. The research reported a range of PGA values, from 0.05 g based on microtremor measurements to 0.57 g calculated using the Indonesian seismic code SNI 1726:2012.…”
Section: Introductionmentioning
confidence: 99%